Climate protection through tradable permits: The EU proposal for a CO2 emissions trading system in Europe - Frank Gagelmann; Bernd Hansjürgens (UFZ-Umweltforschungszentrum Leipzig-Halle, 2002)
On 23 October 2001 the European Commission adopted a proposal for a directive for trade in greenhouse gas emissions. Following the US experience of emissions trading systems, this marks the first large-scale attempt to deploy this instrument of environmental policy in Europe. The proposal places European climate protection policy on a completely new footing. The prospects of its implementation have increased since the climate change conference in Marrakech. This paper introduces the draft directive and gives an initial economic appraisal. It concludes that the directive deliberately and wisely - limits the scope of the first trading phase starting 2005. Consequently, there is still considerable scope for increasing its efficiency (resulting from gains from trading) in later phases, namely by extending both the number of participants and the gases included. The number of participants in the first phase and the institutional arrangements, however, appear sufficient to enable a liquid, functioning market. In this respect, also the politically difficult decision to start with a compulsory system is to be welcomed. Important issues not yet sufficiently clarified include the concrete rules for defining the total permit quantity issued to participants by each Member State, and whether other economic sectors, which are to be treated by other policies and measures, will bear a comparable burden. Furthermore, the essential questions of primary allocation and treatment of newcomers which are in principle left up to Member States as well as the linkage of emissions trading with existing policies affecting the participating sectors must be solved before legal implementation is recommended.
Keywords: 330